FEATURES OF MARKETING MANAGEMENT OF INDUSTRIAL ENTERPRISES - DEMIANENKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the conditions of modern globalization and intense competition, industrial enterprises face numerous challenges that require effective management of marketing activities. This is due to the need to adapt to rapid changes in the market environment, the integration of innovative technologies, meeting the changing needs of consumers and increasing competitiveness. Effective marketing management will allow industrial enterprises to maintain and strengthen their positions in the market, ensuring sustainable development and success in the long term. Industrial enterprises face numerous challenges in a rapidly changing market environment. Effective management of marketing activities becomes a key factor in ensuring their competitiveness and long-term success. The problem is that traditional methods of marketing management may not be effective enough in modern conditions, which requires new approaches and solutions. The problem of managing the marketing activities of industrial enterprises in Ukraine includes numerous aspects that require an integrated approach. In order to function successfully in the modern market environment, enterprises need to implement innovative technologies, adapt to changes in consumer preferences, compete effectively on the market, and develop strategies that can withstand economic and political challenges. Understanding and solving these problems is a key task for ensuring the sustainable development of industrial enterprises. The purpose of the study is to analyze and determine specific approaches and methods of managing the marketing activities of industrial enterprises of Ukraine, as well as to develop recommendations for increasing the effectiveness of marketing strategies in the conditions of a dynamic market environment. Marketing management is a key element of the successful operation of any enterprise. In Ukraine, given the specific economic, political and social conditions, marketing management has its own characteristics and challenges. This section is devoted to the analysis of the main aspects of marketing management of Ukrainian enterprises. At the stage of economic development of Ukraine, the role of managing the marketing activities of a developing company increases. An integral part of effective entrepreneurship is the understanding and use of marketing concepts in business management. The qualitative component of marketing in management is very large, since it determines the rhythm of activity, which is very profitable for business entities. As the practice of Ukrainian companies shows, despite the fact that the implementation of marketing has become more and more widespread, all forms of marketing management are not fully used. And this creates the prerequisites for the competitiveness of companies, adaptation to constant changes in the external environment and market conditions, ensuring the stability of economic conditions. The process of managing material and human resources, ensuring their integration and effective use to achieve the set goals, is known as management. Based on the above, marketing management or marketing management is the process of analyzing, developing and applying tools designed to establish, strengthen and maintain profitable exchanges with customers in a company in order to achieve the company’s objectives of making a profit, increasing sales. volume, increase in market share, etc. Marketing in industrial enterprises has its own unique challenges and features compared to other sectors. In particular, manufactured goods are often characterized by complexity and technical specification, requiring a deep technical understanding of the engineering aspects of the products. Marketing management in industrial enterprises is a complex task that requires the integration of technical knowledge with strategic marketing approaches to achieve success and increase market share. As a result, the marketing management system of an industrial enterprise largely does not meet the requirements of the modern market. Therefore, in order for an enterprise to be able to operate successfully in a turbulent market, the "marketing philosophy" must ensure the presence and functioning of the following three components: strategic approach (focusing the essence of the enterprise’s activities and the energy of all its divisions on achieving higher performance than competitors); market orientation itself; A rigorous process of building and choosing the best strategy, taking into account all the problems faced by industrial enterprises.